Effect of Substitution of Fish Meal with Soybean Meal on Growth Performances and Excreta Moisture Contents During Immunological Stimulation in Male Broiler Chicks - Kazuaki Takahashi; Koichi Matsushita; Yukio Akiba (The Journal of Poultry Science, 2004)
An experiment was conducted to determine effect of substitution of fish meal with soybean meal on growth performances and excreta moisture contents during immunological stimulation induced by injection of Escherichia coli lipopolysaccharide (LPS) and Sephadex in male broiler chicks. Chicks (a day old) were fed either a diet containing plant ingredient only as a plant diet or a diet replaced a part of soybean meal of the plant diet by fish meal as a fish meal diet through the experimental periods. Both diets were formulated to contain most essential nutrients at the recommended levels of the nutrient requirement of the Feeding Standard for Poultry. Birds fed each diet were intraperitoneally injected with LPS at 500μg /kg BW on 14, 16 and 18 days of age and with Sephadex-G50 at 250mg/kg BW on 15 and 17 days of age to simulate immune function, especially macrophage function. Feeding the diet containing fish meal did not affect growth performances and excreta moisture contents as compared with feeding the plant diet before the immune stimulation. However feeding the fish meal diet improved growth performances, water intake to feed intake ratio and reduced excreta moisture content (P=0.07) during the immune stimulation. Water intake to feed intake ratio was significantly lower in chicks fed the diet containing fish meal than that fed the plant diet, regardless of immune stimulation. Ceruloplasmin concentration in plasma of chicks fed the fish meal diet was lower than that of chicks fed the plant diet after LPS injection. The results suggest that feeding diets containing plant sources only does not necessarily assure the same performance and excreta quality as feeding diet containing animal protein sources during immunological stimulation by injection of LPS and Sephadex in male broiler chicks.